Chain code algorithm in deriving T-Junction and region of a freehand sketch - Haron, Habibollah; Shamsuddin, Siti Mariyam; Mohamed, Dzulkifli (Penerbit UTM Press, 2004)
Chain code scheme is one of the Picture Description Languages used to represent lines. This paper focuses on the line drawing interpretation by utilising closed loop chain code algorithm as a tool in deriving two geometric entities, i.e. T-junction and region, of a two-dimensional line drawing sketch. The closed loop chain code algorithm assumes that the sketch represents a three-dimensional solid object. The algorithm is based on 8-connected 3x3 windows of Freeman chain code. Two factors determine the success of the algorithm. The first factor is the direction of traverses either clockwise or anti-clockwise. The other is the start location of the 3x3 window traverse. This paper explains these factors and their applications in deriving the geometric entities. The discussion is supported with an example of L-block object for clarification in the presentation of the algorithm. The paper is concluded with conclusion and future works.